A COHORT STUDY TO COMPARE SURGICAL SITE INFECTION RATE BY USING POVIDONE IODINE PAINT ONLY VS POVIDONE IODINE SCRUB,CHLORHEXIDINE ALCOHOL &POVIDONE IODINE PAINT IN CLEAN GENERAL SURGERIES IN ADULT PATIENTS”: A COHORT STUDY TO COMPARE SURGICAL SITE INFECTION RATE BY USING POVIDONE IODINE PAINT ONLY VS POVIDONE IODINE SCRUB,CHLORHEXIDINE ALCOHOL &POVIDONE IODINE PAINT IN CLEAN GENERAL SURGERIES IN ADULT PATIENTS” (Bombay Hospital Journal, 2024)
The normal skin of healthy human beings harbors a rich bacterial flora, is an established fact now. Normally considered non-pathogenic, these organisms may be a potential source of infection of the surgical site or wound. Postoperative infections at operative site remain a major source of illness and a less frequent cause of death in the surgical patient. Such infections lengthen bed stay of the patient and results in higher costs. To remove transient as well as pathogenic micro-organisms on the skin surface and to reduce the resident flora, is the goal of surgical skin preparation with antiseptics. Povidone iodine (iodophors) and chlorhexidine are the most often used antiseptics for skin preparation preoperatively in clean and clean-contaminated general surgeries
Keywords: Povidone Iodine paint, povidone iodine scrub, chlorhexidine, skin disinfection